On the persistency of crater assignment criteria for Stromboli explosion-quakes - F. Iacop; R. Carniel (Annals of Geophysics, 1996)
On the basis of the results of previous works by our group, this paper aims to investigate the correlation between features of a kind of seismic events recorded at Stromboli (the so called explosion-quakes) and the source of such explosions, i.e. the different craters. The purpose is that of finding parameters in order to try an automatic assignment of new events to their crater of origin. These parameters must be searched for both in time and in frequency domain. Afterwards the stability in time of the discrimination is discussed. An important « side effect» of this analysis is the discovery that the percentage of summital explosions not producing seismic signals recordable by a 2 s seismometer is not negligible.